Correlation between Workload and Work Environment with Work Stress - Shabrina Firsta Aulia1 , Putri Ayuni Alayyannur2 , Endang Dwiyanti3 , Tri Martiana4 , Shintia Yunita (Institute of Medico-legal Publications Pvt Ltd, 2021)
Competition in the business world nowadays caused many pressures on workers and resulting in work stress.During 2001, the problem of stress had cost the organization up to 300 billion in terms of reimbursingmaintenance costs, workers’ compensation, absenteeism and labor turnover. In Indonesia, especially Jakarta,around 1.33 million residents experience stress. This figure reaches 14% of the total population with severestress levels of 7-10% and acute stress of 1-3%. It was also reported that Health care costs were almost 50%higher for treating workers who experienced high levels of stress in their work. Previous studies had foundout that work stress was caused by several factors including work environment and workload. The purposeof this study was to analyze the correlation between workload and work environment with work stress on theMaintenance and Repair Division workers of PT. PAL Indonesia (Persero). This research design was a crosssectional study. The population in this study were all technician workers on the Maintenance and RepairDivision of PT. PAL Indonesia (Persero) as many as 51 workers. The sample was calculated using a simplerandom sampling technique so that a sample of 49 workers was obtained in the Production Department,Maintenance and Repair Division of PT. PAL Indonesia (Persero). The study was conducted in June 2019.Variables in this study were work climate, noise, lighting, physical workload, mental workload, and workstress. The data were analyzed by using the chi-square test and spearman test because there are differencesin the scale of the data on the variables. The results are: work climate is not related to work stress (sig 0.715> ?), noise is not related to work stress (sig 0.380 > ?), lighting is not related to work stress (0.322 > ?),physical workload is related to work stress (sig 0.004 < ?), mental workload has no relationship with workstress (sig 0.377 > ?). The conclusion of this study is that only physical workload has a correlation withwork stress.